44 Improving standards in the follow-up of fontan patients. (2nd February 2018) - Sodhi, Jaskiran Kaur; Witter, Thomas; Bell, Aaron; Bellsham-Revell, Hannah
Abstract : Purpose: Increasing children survive staged Fontan palliation and structured follow-up is becoming increasingly important. We assessed how these patients are currently followed-up, to design a more robust system ensuring the multi-organ impact of the Fontan circulation is adequately assessed, allowing early optimisation and treatment of complications. Methods: Patients who had undergone Fontan completion prior to 16 years were identified and post-Fontan investigations recorded. Cardiac MRI, cardiac MRI catheterization (used as the primary diagnostic invasive technique in our institution), exercise tests (both treadmill and cardiopulmonary exercise test, CPET) and abdominal ultrasound were recorded. Results: 367 patients were identified – 69 were excluded as followed-up at other cardiac centres. 126 (42%) had a cardiac MRI, 37 (12%) cardiac catheterisation and 22 cardiac MRI and MRI catheter. The median (range) of the first MRI was 5.6 (0.01–13.2) years and 4.6 (0.04–10.3) years for MRI cardiac catheterization. CPET were performed later with at a median of 8.8 (0.8–14.9) years. 16 (5%) patients had a one-off abdominal ultrasound scan, with a further 8 (2%) patients who had multiple ultrasound scans. Conclusion: This review demonstrates wide variation in referral practice for investigations and relatively low use of CPET. This may be related to the minimum height requirement of the exercise bike, or that patients are not being referred until they are symptomatic. Internationally there is a move to formalised Fontan follow-up with recognition of the multi-organ complications and early intervention. Based on this audit we are designing a single-ventricle programme to try to achieve these aims.